School Breakfast Program and School Performance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The effects of participation in the school breakfast program by low income children on academic achievement and rates of absence and tardiness are reported from the Department of Pediatrics, Boston City Hospital, Boston, MA.